Hypnotic Relaxation Therapy and Sexual Function in PostmenopausalWomen: Results of a Randomized Clinical Trial. Issue 2 (2nd April 2016) - Johnson, Aimee K.; Johnson, Alisa J.; Barton, Debra; Elkins, Gary
Abstract: Sexual dysfunction is a common problem for postmenopausal women. This study, as part of a larger randomized controlled trial, examined the effect of hypnotic relaxation therapy on sexual dysfunction, a secondary study outcome, in postmenopausal women. Sexual function was assessed using the Sexual Activity Questionnaire (SAQ). Significant improvement in sexual pleasure and discomfort were reported following 5 weekly sessions of hypnotic relaxation therapy, compared with those receiving an attention control. Total SAQ scores showed significant improvement in the hypnotic relaxation therapy treatment group while holding baseline SAQ scores constant. Improvements showed a slight increase at the Week 12 follow-up. The results of this analysis provide initial support for the use of hypnotic relaxation therapy to improve sexual function in postmenopausal women.